2019
DOI: 10.1159/000500610
|View full text |Cite
|
Sign up to set email alerts
|

Ivy Sign Predicts Ischemic Stroke Recurrence in Adult Moyamoya Patients without Revascularization Surgery

Abstract: Background: Although there is a standard guideline for performing revascularization surgery in patients with Moyamoya diseases (MMD), more objective and easily obtainable predictors are still needed. Objectives: In this study, we aimed to evaluate the relationship between an ipsilateral ivy sign and ischemic stroke recurrence in adult MMD patients without revascularization surgery. Methods: We included consecutive MMD patients without revascularization surgery between 2006 and 2014. The ivy sign was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…65 However, there are limited data addressing the question of prognosis between MMD patients with and without ivy sign under conservative treatment, although the "Ivy sign (+) group" showed a higher ischemic recurrence rate than did the "Ivy sign (-) group" in Nam et al's study. 31 (4) In previous studies, perfusion "abnormalities" are reported to correspond to ivy sign dominant regions. While perfusion parameters such as CVR, CBF, CBV, and OEF may reflect an abnormality, clinical relevance between ivy sign and perfusion "abnormalities" is not yet clear.…”
Section: Future Prospectsmentioning
confidence: 97%
See 4 more Smart Citations
“…65 However, there are limited data addressing the question of prognosis between MMD patients with and without ivy sign under conservative treatment, although the "Ivy sign (+) group" showed a higher ischemic recurrence rate than did the "Ivy sign (-) group" in Nam et al's study. 31 (4) In previous studies, perfusion "abnormalities" are reported to correspond to ivy sign dominant regions. While perfusion parameters such as CVR, CBF, CBV, and OEF may reflect an abnormality, clinical relevance between ivy sign and perfusion "abnormalities" is not yet clear.…”
Section: Future Prospectsmentioning
confidence: 97%
“…23 These were confirmed by subsequent studies. 20,24,31 By using positron emission tomography, Vuignie et al also found that ivy sign was significantly correlated with the increase OEF. 23 Consistently, the improvement of CVR after direct or indirect bypass surgery brought about a decrease in ivy sign.…”
Section: Angiographymentioning
confidence: 97%
See 3 more Smart Citations